Soil and environmental analysis : (Marcel Dekker, Inc., 2004)
Incorporating coverage of the most modern instruments and methods, this worthy Third Edition cites hundreds of published works to authoritatively span analysis of organic pollutants in the environment through measurement of trace gases. Features numerous illustrative figures, tables, and equations!